Clinical Characteristics and Diagnostic Imaging of Low Back Pain: A Systematic Review - Bonita, Nita; Dwi Pratiwi; Muh Yasin Arsal; Erlin Syahril; Raden Selma (HM Publisher, 2024)
Low back pain (LBP) is a prevalent and debilitating condition with diverse clinical presentations and etiologies. This systematic review aimed to synthesize the current literature on the clinical characteristics and diagnostic imaging findings associated with LBP, providing a comprehensive overview of this multifaceted condition. A systematic search of electronic databases was conducted, encompassing studies published between 2018 and 2023. Studies reporting on clinical characteristics (pain location, duration, severity, radiation, associated symptoms) and diagnostic imaging findings (X-ray, CT, MRI) in LBP patients were included. Data extraction and quality assessment were performed independently by two reviewers. Twenty studies, with a total of 9,232 patients, were included. The most common clinical presentation was localized LBP (85%), followed by pain duration of less than 3 months (60%) and moderate pain severity (55%). Radicular pain and neurological deficits were reported in a significant minority of patients (20% and 15%, respectively). The most frequent imaging finding was degenerative changes (40-70%), followed by disc herniation (20-35%) and spondylolisthesis (5-12%). Other less frequent findings included spinal stenosis, compression fractures, and tumors. This review highlights the heterogeneity of clinical presentations and imaging findings in LBP. While localized LBP is predominant, a substantial proportion of patients experience radicular pain and neurological deficits. Degenerative changes are the most frequent imaging finding, followed by disc herniation. The choice of imaging modality should be guided by clinical presentation and suspected etiology.